An Analytical Study of Physicians Behaviour Towards Marketing of Pharmaceutical Products - Arora, Usha; Taneja, Girish (Indian Journal of Marketing, 2006)
Physicians are perhaps the most important players in pharmaceutical sales. They write the prescriptions that determine which drugs will be used by the patient. Influencing the physician is key to pharmaceutical sales.This paper explores Indian pharmaceutical marketing system, physicians expectations from pharmaceutical company and the major factors that influence a physician for prescribing a product of a particular company. A Survey of 100 physicians from 10 districts of Haryana was done to meet out the objectives. A close ended questionnaire was prepared and got it filled from the chosen physicians. Good quality, widely available product at reasonable price is foremost expectation of physician from pharmaceutical company. A regular visit by good personality medical representative is best tool of promotion for a pharmaceutical company. Literatures, journals and sponsorship for conferences are preferable promotion tools in comparison to organization of free camps, personal gifts, medicine samples or any other incentive. Physicians can easily recall short brand name related to molecule disease or organization.